'Prion‐like' propagation of the synucleinopathy of M83 transgenic mice depends on the mouse genotype and type of inoculum. Issue 1 (5th September 2017) - Sargent, Dorian; Verchère, Jérémy; Lazizzera, Corinne; Gaillard, Damien; Lakhdar, Latifa; Streichenberger, Nathalie; Morignat, Eric; Bétemps, Dominique; Baron, Thierry
Abstract: The M83 transgenic mouse is a model of human synucleinopathies that develops severe motor impairment correlated with accumulation of the pathological Ser129‐phosphorylated α‐synuclein (α‐syn P ) in the brain and spinal cord. M83 disease can be accelerated by intracerebral inoculation of brain extracts from sick M83 mice. This has also recently been described using peripheral routes, injecting recombinant preformed α‐syn fibrils into the muscle or the peritoneum. Here, we inoculated homozygous and/or hemizygous M83 neonates via the intraperitoneal and/or intracerebral routes with two different brain extracts: one from sick M83 mice inoculated with brain extract from other sick M83 mice, and the other derived from a human multiple system atrophy source passaged in M83 mice. Detection of α‐syn P using ELISA and western blot confirmed the disease in mice. The distribution of α‐syn P in the central nervous system was similar, independently of the inoculum or inoculation route, consistent with previous studies describing M83 disease. ELISA tests revealed higher levels of α‐syn P in homozygous than in hemizygous sick M83 mice, at least after IC inoculation. Interestingly, the immunoreactivity of α‐syn P detected by ELISA was significantly lower in M83 mice inoculated with the multiple system atrophy inoculum than in M83 mice inoculated with the M83 inoculum, at the first two passages. 'Prion‐like' propagation of the synucleinopathy up to the clinical disease was accelerated by both intracerebral and intraperitoneal inoculations of brain extracts from sick mice. This acceleration, however, depends on the levels of α‐syn expression by the mouse and the type of inoculum. Abstract : The transgenic M83 mouse is a model of human synucleinopathies. M83 mice develop a severe motor impairment, associated with the accumulation of pathological Ser129‐phosphorylated α‐synuclein (α‐syn P ) in the brain and the spinal cord. Here, we show that intraperitoneal inoculation of sick M83 brain homogenate accelerates the M83 disease. The accumulation of α‐syn P detected by ELISA tests depends on the level of expression of the α‐synuclein in the mouse brain and the type of inoculum used.